Enhancing Zakat Learning Outcomes Using Augmented Reality and Virtual Reality Technologies - Choiri, Muttaqin; Setiawan, Firman; Shofiyuddin, Ahmad (Aptisi Transactions On Technopreneurship (ATT), 2025)
This research aims to develop a learning module for Zakat material based on AR technology combined with VR to improve student learning outcomes in alignment with the Independent Learning Independent Curriculum. The research method uses the Research and Development (RnD) approach, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation (ADDIE). The developed product was validated by material experts and media experts, receiving scores of 90.8% and 90.5%, respectively, and tested on students from four higher education institutions in East Java: University of Trunojoyo Madura, Nahdlatul Ulama Sunan Giri University, Nahdlatul Ulama Surabaya University, and Al-Khozini Sidoarjo Islamic Religious Institute. The first trial was conducted in a small class and produced an average score of 85.4%, followed by a large-class trial with an average score of 83.3%. In comparison, previous test results using a conventional module produced an average score of 72, which increased to an average of 86 when students used the Zakat module based on augmented reality combined with virtual reality. Thus, the results show that the AR and VR technology-based module for Zakat material has a positive impact on student learning outcomes in higher education institutions.